Youth Heavy Metal Bands in Morocco: Resistance and the Struggle for Change - El Harami, Said; Yachoulti, Mohammed (European Scientific Journal, ESJ, 2023)
In Morocco, Metal is a controversial genre of youth music that has usually been misinterpreted, marginalized and stigmatized by many individuals due to its transgressive sound, lyrical contents and visual codes. In his regard, the purpose of this paper is to explore the specific lyrical themes of Moroccan Metal bands in relation to elements of symbolic transgression and musical activism. It also aims to the main motivations that push these bands to produce and sustain their musical discourse taking into account the conservative nature of the Moroccan context. Using both content analysis and semi-structured interviews, the paper concluded that despite the severe cultural challenges that surround their socio-cultural condition, the artistic participation of Moroccan Metal bands have not just allowed them to gain support from their subculture but also made them impose themselves as leaders of culture of courage. By tracing the Moroccan Metal bands’ artistic engagement and commitments, this paper will bring to light the cultural sociology and multi-dimensional nature of Metal narratives in Morocco and the challenges that shape its existence. It also provides an interesting account for students and academics concerned with cultural minorities, literature and arts-related topics about the nature of content produced by this minority as a reference.